A PERBANDINGAN LEMBAGA PENYELENGGARA PEMILIHAN UMUM ANTARA NEGARA FILIPINA DENGAN NEGARA INDONESIA (Jurnal Nawala Politika, 2023)
Indonesia and the Philippines had previously been led by authoritarian regimes, but the authoritarian regime in Indonesia ended in 1998 through reform, while the Philippines ended in 1986 after the EDSA I revolution. However, after EDSA I democracy in the Philippines did not go well until EDSA II emerged. . After EDSA II of the Philippines and Indonesia's reforms, the two countries are moving towards a better democracy through elections. Both carried out more democratic elections in 2004- This study aims to compare elections using three comparative indicators, namely the electoral system, party system, and voter political participation. This study uses a comparative analysis method, with data collection through literature review. The results of this study indicate that there are similarities and differences that occur in the two countries. The similarities between the two countries are election management bodies, direct elections, the use of a multiparty system, while the differences are in the voting system, ballot papers, election methods, the number of DPT and the tenure of public officials who are elected through elections. Based on these similarities and differences, it shows that the Philippines has a higher level of democracy than Indonesia.